Autoimmune hepatitis in a patient with human immunodeficiency virus: Case report (Research, Society and Development, 2025)
Autoimmune hepatitis (AIH) is a chronic liver disease that predominantly affects women, characterized by hypergammaglobulinemia, positivity for autoantibodies, and histological changes in the liver. Without treatment, it can progress to cirrhosis and liver failure. Immune reconstitution inflammatory syndrome (IRIS), which occurs after the initiation of antiretroviral therapy in patients with HIV (human immunodeficiency virus), can trigger AIH in individuals with a genetic predisposition to autoimmune diseases. IRIS leads to an intensification of inflammatory symptoms due to the immune system overreacting to pre-existing opportunistic infections. This article aims to present a case report of a patient living with HIV who developed AIH after starting antiretroviral therapy. Clinical management with immunosuppressants proved to be effective, highlighting the importance of continuous monitoring for the early identification of associated complications and appropriate therapeutic adjustment.